Crop-soil simulation models : applications in developing countries - Matthews, Robin B.; Stephens, William, Ph. D. (CABI Pub., 2002)
This book, based on work sponsored by the Natural Resources Systems Programme of the UK Department for International Development, reviews progress in crop-soil simulation modelling and assesses its application to agriculture in developing countries. The books is divided into sections based on a classification of models with different functions: those used as tools by researchers; those used as tools by decision-makers; and those used in education, training and technology transfer. The examples used are mainly from applications of crop models in developing countries, supplemented by experiences with tropical crops in Australia. The final sections of the book discuss whether crop models have proved useful and consider the way forward in crop modelling and application.